Coated paper cup body paper and production process thereof
By using mixed fiber slurry of bamboo pulp fiber, broadleaf wood pulp fiber and needle wood pulp fiber in the production process of coated paper cup base paper, the problem of expansion rate control of coated paper cup base paper is solved, and the problem of coating paper cup base paper is improved. The paper's tear resistance and dimensional stability are achieved, achieving better mechanical properties and durability.
Patent Information
- Application Number
- CN202411282080.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
The expansion rate of existing coated paper cups is not easy to control, resulting in poor dimensional stability of the final product.
A mixed fiber slurry of bamboo pulp fiber, bleached broadleaf wood pulp fiber and bleached needle wood pulp fiber, and lignin sulfonate, wet strength agent and silanized modified glass powder are added to the slurry, and the fabrication is made through the Internet. , Press and dehydrate, dry, calendering and glue application processes to prepare coated paper cup base paper, control the fiber structure and filler distribution to reduce the expansion rate.
Improves the tear resistance and dimensional stability of the paper, while enhancing the mechanical properties, ensuring the dimensional stability and durability of the paper cup.
Smart Images

Figure BDA0005041956830000091 
Figure BDA0005041956830000092
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of packaging materials, and in particular to a coated paper cup base paper and a production process thereof. Background Art
[0002] For paper cup products, the quality of base paper has an important influence on the performance and quality of paper cup products. In the prior art, base paper (white paperboard) made of chemical wood pulp is usually used as the main material of paper cups. This base paper needs to have good hardness and stiffness. For paper cups that need to hold hot drinks, it is also necessary to coat the base paper. Coating is to coat a layer of polymer film (such as polyethylene) evenly on the surface of the base paper (can be single-sided or double-sided) through a coating machine to enhance the waterproofness and heat resistance of the paper cup. After the coating is completed, a slitting machine is needed to cut the coated paper into paper sheets and roll paper according to certain specifications. The paper sheets are used to make the cup body of the paper cup, and the roll paper is used to make the bottom of the paper cup. After the slitting is completed, various patterns and texts can also be printed on the paper sheets using an offset printing machine or a gravure printing machine. Finally, the paper sheets and roll paper are placed in a paper cup forming machine, the paper sheets are bent and pressed on the mold, and then bonded to the cup bottom roll to form a complete paper cup.
[0003] The base paper used to make coated paper cups needs to have good whiteness, water resistance, and mechanical properties (especially tensile strength, bursting resistance, and tear resistance). In addition, the base paper used to make coated paper cups needs to have a low shrinkage rate to ensure good dimensional stability of the final product. At present, one of the shortcomings of the prior art is that the shrinkage rate of the base paper is not easy to control, and a high shrinkage rate will reduce the dimensional stability of the final product. Summary of the invention
[0004] One of the problems solved by the present invention is how to provide a coated paper cup base paper with a lower shrinkage rate.
[0005] In order to solve at least one of the above problems, the present invention provides a production process of coated paper cup base paper, which comprises:
[0006] S100, pulping raw materials including bamboo pulp fiber, bleached hardwood pulp fiber, and bleached coniferous wood pulp fiber respectively, mixing and refining the raw materials to obtain fiber pulp;
[0007] S200, sending the fiber slurry into a slurry preparation tank, adding lignin sulfonate, wet strength agent, glass powder, and aluminum sulfate to obtain a mixed slurry;
[0008] S300, the mixed slurry is subjected to screen papermaking, pressing and dehydrating, drying, calendering, and sizing to obtain coated paper cup base paper;
[0009] The glass powder is modified by silanization.
[0010] In any of the above technical solutions, S100 specifically includes:
[0011] S110, weighing 5 to 10 parts by mass of bamboo pulp fiber, 15 to 20 parts by mass of bleached hardwood pulp fiber, and 100 parts by mass of bleached coniferous wood pulp fiber;
[0012] S120, beating the bamboo pulp fibers to a temperature of 30°SR to 35°SR to obtain bamboo pulp;
[0013] S130, beating the bleached hardwood pulp fibers and the bleached softwood pulp fibers to 28°SR to 32°SR, respectively, to obtain hardwood pulp and softwood pulp;
[0014] S140, mixing bamboo pulp, hardwood pulp and coniferous wood pulp, and refining the pulp to 38°SR to 42°SR to obtain fiber pulp.
[0015] In any of the above technical solutions, S200 specifically includes:
[0016] S210, weighing 2 to 4 parts by mass of lignin sulfonate, 2 to 4 parts by mass of wet strength agent, and 5 to 10 parts by mass of glass powder;
[0017] S220, sending the fiber slurry into a slurry mixing tank, first adding lignin sulfonate and wet strength agent and mixing evenly, then adding glass powder, and finally gradually adding aluminum sulfate until the pH value is adjusted to 7.5 to 8.5 to obtain a mixed slurry.
[0018] In any of the above technical solutions, the glass powder is fluorophosphate glass powder.
[0019] In any of the above technical solutions, the glass powder is prepared by the following steps:
[0020] S410, weighing materials according to the molar percentage of sodium fluoride: magnesium fluoride: calcium fluoride: aluminum oxide: phosphorus pentoxide = (12-14): (6-10): (8-12): (15-20): (45-55), grinding and mixing them evenly to obtain a glass matrix;
[0021] S420, heating and melting the glass matrix to obtain glass liquid;
[0022] S430, casting the glass liquid into a shape, and annealing it to obtain a glass body;
[0023] S440, crushing and grinding the glass body to obtain glass powder.
[0024] In any of the above technical solutions, the temperature condition for heating and melting is 1280° C. to 1350° C., and the time for heating and melting is 1 h to 1.5 h.
[0025] In any of the above technical solutions, the annealing temperature condition is 500° C. to 550° C., and the annealing time is 2 h to 3 h.
[0026] In any of the above technical solutions, the silanization modification treatment is carried out by the following steps:
[0027] S510, mixing acetic acid, water, and 3-aminopropyltriethoxysilane in a mass ratio of acetic acid: water: 3-aminopropyltriethoxysilane = (10-20): (40-60): 100, and uniformly stirring to obtain a silane hydrolyzate;
[0028] S520, adding glass powder to silane hydrolyzate according to a mass ratio of glass powder to silane hydrolyzate = (20-25): 100 to obtain a suspension;
[0029] S530. Add N,N-dimethyl oxalic acid and dimethyl sulfate to the suspension in a mass ratio of N,N-dimethyl oxalic acid: dimethyl sulfate: glass powder = (4-6): (4-6): (20-25) to react and obtain glass powder that has been subjected to silanization modification.
[0030] In any of the above technical solutions, S530 specifically includes:
[0031] S531, sending the suspension into a reaction kettle, heating it to 40°C to 45°C, and stirring the reaction for 3h to 4h;
[0032] S532, adding N,N-dimethyl oxalic acid and toluene 4 to 5 times the mass of N,N-dimethyl oxalic acid into a reaction kettle, stirring and reacting at a temperature of 100° C. to 120° C. for 3 h to 4 h, and distilling off toluene under reduced pressure;
[0033] S533, adding dimethyl sulfate and acetone in an amount 4 to 5 times the amount of dimethyl sulfate into a reaction kettle, stirring the reaction at a temperature of 80° C. to 100° C. for 0.5 h to 1 h, and evaporating the acetone under reduced pressure to obtain glass powder that has been subjected to silanization modification.
[0034] The present invention also provides a coated paper cup base paper, which is obtained by adopting the production process of any one of the above technical solutions.
[0035] Beneficial Effects
[0036] The present invention provides a production process for coated paper cup base paper, which comprises firstly beating raw materials including bamboo pulp fiber, bleached hardwood pulp fiber and bleached softwood pulp fiber respectively, mixing and grinding to obtain fiber pulp. Then the fiber pulp is sent to a pulping tank, lignin sulfonate, wet strength agent, glass powder and aluminum sulfate are added to obtain a mixed pulp. Finally, the mixed pulp is subjected to screen papermaking, pressing and dehydration, drying, calendering and sizing to obtain coated paper cup base paper. In the technical scheme of the present invention, the length of the softwood pulp fiber is relatively long (usually between 2.5 mm and 4 mm), which makes the paper have higher strength and durability. In addition, the long fibers of the softwood pulp fiber can be better interwoven to form a tighter structure, thereby enhancing the compression resistance and tear resistance of the paper. By adding hardwood pulp fibers to the softwood pulp fibers, the gaps between the softwood pulp fibers can be filled with shorter hardwood pulp fibers to enhance the bonding force between the fibers. Thus, the expansion rate of the paper can be reduced while ensuring that the paper has good tear resistance. In addition, considering that wood pulp fibers have a large degree of expansion and contraction, the present invention adds bamboo pulp fibers with relatively poor water absorption performance to the slurry, and adds non-hygroscopic glass powder to improve the problem of large expansion and contraction of paper. In addition, glass powder, as an inorganic filler, also has a reinforcing effect and can improve the mechanical strength of paper. The glass powder treated with silanization has better dispersibility and can better combine with plant fibers, thereby further improving the dimensional stability and mechanical properties of paper. DETAILED DESCRIPTION
[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description of the specific embodiments of the present invention.
[0038] Unless otherwise specified, the reagents and raw materials used in the present invention can be purchased through commercial channels. The experimental methods in the following examples without specifying specific conditions are selected according to conventional methods and conditions, or according to the product specifications.
[0039] The embodiment of the present invention provides a production process for coated paper cup base paper, and the production process adopted by the present invention includes:
[0040] S100, pulping raw materials including bamboo pulp fiber, bleached hardwood pulp fiber, and bleached coniferous wood pulp fiber respectively, mixing and refining the raw materials to obtain fiber pulp;
[0041] S200, sending the fiber slurry into a slurry preparation tank, adding lignin sulfonate, wet strength agent, glass powder, and aluminum sulfate to obtain a mixed slurry;
[0042] S300, the mixed slurry is subjected to screen papermaking, pressing and dehydrating, drying, calendering, and sizing to obtain coated paper cup base paper;
[0043] The glass powder is modified by silanization.
[0044] In some implementations of the present invention, S100 specifically includes:
[0045] S110, weighing 5 to 10 parts by mass of bamboo pulp fiber, 15 to 20 parts by mass of bleached hardwood pulp fiber, and 100 parts by mass of bleached coniferous wood pulp fiber;
[0046] S120, beating the bamboo pulp fibers to a temperature of 30°SR to 35°SR to obtain bamboo pulp;
[0047] S130, beating the bleached hardwood pulp fibers and the bleached softwood pulp fibers to 28°SR to 32°SR, respectively, to obtain hardwood pulp and softwood pulp;
[0048] S140, mixing bamboo pulp, hardwood pulp and coniferous wood pulp, and refining the pulp to 38°SR to 42°SR to obtain fiber pulp.
[0049] Preferably, in some embodiments of the present invention, in S110, 8 parts by mass of bamboo pulp fiber, 16 parts by mass of bleached hardwood pulp fiber, and 100 parts by mass of bleached coniferous wood pulp fiber are weighed.
[0050] In the above steps, since the coniferous wood pulp fibers are longer and the long fibers can be better interwoven to form a tighter structure, the coniferous wood pulp fibers can make the paper have higher strength, durability, compression resistance and tear resistance. The length of the broadleaf wood pulp fibers is shorter, and they can fill the gaps between the coniferous wood pulp fibers and enhance the bonding force between the fibers. The water absorption rate of the bamboo pulp fibers is lower, and they can reduce the expansion rate of the paper. Therefore, after the fiber slurry prepared by S100 is made into base paper, the mechanical properties are better and the expansion rate is lower.
[0051] In some implementations of the present invention, S200 specifically includes:
[0052] S210, weighing 2 to 4 parts by mass of lignin sulfonate, 2 to 4 parts by mass of wet strength agent, and 5 to 10 parts by mass of glass powder;
[0053] S220, sending the fiber slurry into a slurry mixing tank, first adding lignin sulfonate and wet strength agent and mixing evenly, then adding glass powder, and finally gradually adding aluminum sulfate until the pH value is adjusted to 7.5 to 8.5 to obtain a mixed slurry.
[0054] Preferably, in some embodiments of the present invention, in S210, 2 parts by mass of lignin sulfonate, 3 parts by mass of wet strength agent, and 8 parts by mass of glass powder are weighed.
[0055] During the papermaking and pulping process, wet strength agents will adsorb to the negative charges on the fiber surface to form a cross-linked resin network or gel. These substances can reduce the swelling degree of the fibers and increase the bonding force between the fibers, thereby improving the wet strength of the paper. In addition to wet strength, wet strength agents can also improve the mechanical properties of the paper, such as tensile strength and tear strength. The improvement of these properties makes the paper more durable and reliable, and can meet a wider range of application requirements. Preferably, the present invention can use a cationic wet strength agent such as polyamide-epichlorohydrin resin (PAE) or polyethyleneimine (PEI).
[0056] In the prior art, the control of the performance parameters of base paper such as whiteness, water resistance, and mechanical properties can be achieved by adding fillers and adjusting their components. For example, the whiteness and antibacterial properties of base paper can be adjusted by adding titanium dioxide, the mechanical properties of base paper can be improved by adding calcium carbonate, and the performance parameters of base paper in various aspects can be improved in a targeted manner by adding a series of various inorganic fillers such as glass fiber, porcelain powder, talcum powder, montmorillonite, etc. The present invention uses glass powder as a filler, and the role of glass powder as a filler is. It can provide a significant reinforcement effect for paper, so that it has better tensile, twisting and tearing resistance. In addition, glass powder has good waterproof and moisture-proof properties, and its addition to pulp can significantly improve the waterproof and moisture-proof capabilities of paper. Finally, non-hygroscopic glass powder can further reduce the expansion and contraction rate of paper.
[0057] Preferably, in some embodiments of the present invention, the glass powder is a fluorophosphate glass powder. The glass powder used in the present invention is prepared by the following steps:
[0058] S410, weighing materials according to the molar percentage of sodium fluoride: magnesium fluoride: calcium fluoride: aluminum oxide: phosphorus pentoxide = (12-14): (6-10): (8-12): (15-20): (45-55), grinding and mixing them evenly to obtain a glass matrix;
[0059] S420, heating and melting the glass matrix to obtain glass liquid;
[0060] S430, casting the glass liquid into a shape, and annealing it to obtain a glass body;
[0061] S440, crushing and grinding the glass body to obtain glass powder.
[0062] Preferably, in S410, sodium fluoride:magnesium fluoride:calcium fluoride:aluminum oxide:phosphorus pentoxide=12:6:12:20:50.
[0063] The temperature of the heating and melting is 1280° C. to 1350° C., and the time of the heating and melting is 1 h to 1.5 h. The temperature of the annealing is 500° C. to 550° C., and the time of the annealing is 2 h to 3 h.
[0064] Fluorophosphate glass has higher hardness and lower thermal expansion coefficient, smaller dimensional changes due to temperature changes, and better stability.
[0065] Furthermore, the present invention performs a silanization modification treatment on the glass powder. Specifically, in some embodiments of the present invention, the silanization modification treatment is performed by the following steps:
[0066] S510, mixing acetic acid, water, and 3-aminopropyltriethoxysilane in a mass ratio of acetic acid: water: 3-aminopropyltriethoxysilane = (10-20): (40-60): 100, and uniformly stirring to obtain a silane hydrolyzate;
[0067] S520, adding glass powder to silane hydrolyzate according to a mass ratio of glass powder to silane hydrolyzate = (20-25): 100 to obtain a suspension;
[0068] S530. Add N,N-dimethyl oxalic acid and dimethyl sulfate to the suspension in a mass ratio of N,N-dimethyl oxalic acid: dimethyl sulfate: glass powder = (4-6): (4-6): (20-25) to react and obtain glass powder that has been subjected to silanization modification.
[0069] Preferably, in S530 , N,N-dimethyloxalic acid: dimethyl sulfate: glass powder = 5:5:20.
[0070] Among them, S530 specifically includes:
[0071] S531, sending the suspension into a reaction kettle, heating it to 40°C to 45°C, and stirring the reaction for 3h to 4h;
[0072] S532, adding N,N-dimethyl oxalic acid and toluene 4 to 5 times the mass of N,N-dimethyl oxalic acid into a reaction kettle, stirring and reacting at a temperature of 100° C. to 120° C. for 3 h to 4 h, and distilling off toluene under reduced pressure;
[0073] S533, adding dimethyl sulfate and acetone in an amount 4 to 5 times the amount of dimethyl sulfate into a reaction kettle, stirring the reaction at a temperature of 80° C. to 100° C. for 0.5 h to 1 h, and evaporating the acetone under reduced pressure to obtain glass powder that has been subjected to silanization modification.
[0074] The purpose of the above steps is to use 3-aminopropyltriethoxysilane to perform silane coupling treatment on the glass powder, and then reduce the surface energy of the glass powder through the condensation reaction between N,N-dimethyloxalic acid and dimethyl sulfate. The glass powder after the above silanization modification has better dispersibility and can better combine with plant fibers, thereby further improving the dimensional stability and mechanical properties of paper.
[0075] Example 1
[0076] In this example, a series of coated paper cup base paper samples were prepared, and the raw material ratios thereof are shown in Table 1. The specific preparation steps are as follows:
[0077] S1. According to the mass ratio in Table 1, weigh bamboo pulp fiber, bleached hardwood pulp fiber, and bleached coniferous pulp fiber; beat the bamboo pulp fiber to 32°SR to obtain bamboo pulp; beat the bleached hardwood pulp fiber and the bleached coniferous pulp fiber to 30°SR to obtain hardwood pulp and coniferous pulp respectively; mix the bamboo pulp, hardwood pulp, and coniferous pulp, and grind them to 40°SR to obtain fiber pulp;
[0078] S2. Sodium fluoride, magnesium fluoride, calcium fluoride, aluminum oxide, and phosphorus pentoxide are weighed according to the molar ratio in Table 1, and mixed evenly in a planetary ball mill to obtain a glass matrix; the glass matrix is sent into a muffle furnace, heated and melted at 1300° C. for 1.5 hours to obtain a glass liquid; the glass liquid is cast into an alumina mold, and annealed at 520° C. for 3 hours to obtain a glass body; the glass body is crushed and ground to obtain a glass powder with a D50 of 5 μm;
[0079] S3. Acetic acid, water and 3-aminopropyltriethoxysilane are mixed and stirred evenly at a mass ratio of acetic acid: water: 3-aminopropyltriethoxysilane = 15:50:100 to obtain a silane hydrolyzate; glass powder is added to the silane hydrolyzate at a mass ratio of glass powder: silane hydrolyzate = 25:100 to obtain a suspension; the suspension is sent to a reactor, heated to 42°C, and stirred for reaction for 3 hours; N,N-dimethyl oxalic acid and toluene 4 times the mass of N,N-dimethyl oxalic acid are added to the reactor according to the mass ratio in Table 1, stirred for reaction at 110°C for 3 hours, and toluene is evaporated under reduced pressure; dimethyl sulfate and acetone 4 times the mass of dimethyl sulfate are added to the reactor, stirred for reaction at 90°C for 1 hour, and acetone is evaporated under reduced pressure to obtain glass powder modified by silanization;
[0080] S4. Weigh 2 parts by mass of lignin sulfonate, 3 parts by mass of wet strength agent, and 8 parts by mass of glass powder; send the fiber slurry into a pulp mixing tank, first add lignin sulfonate and wet strength agent and mix evenly, then add glass powder, and finally gradually add aluminum sulfate until the pH value is adjusted to 7.5 to obtain a mixed slurry; put the mixed slurry on the screen for papermaking, press dehydration, drying, calendering, and sizing to obtain a sample of coated paper cup base paper.
[0081] Table 1
[0082]
[0083] The absorption rate of samples 1 to 4 was tested by GB / T1540 Determination of water absorption of paper and paperboard (Kebo method); the tensile strength of samples 1 to 4 was tested by GB / T 12914 Determination of tensile strength of paper and paperboard (constant rate tensile method); the elongation of samples 1 to 4 was tested by ISO1924-2-2013 Paper and paperboard. Determination of tensile properties. The test results are shown in Table 2.
[0084] Table 2
[0085]
[0086]
[0087] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A production process for coated paper cup base paper, It is characterized in that The production process comprises: S100, pulping raw materials including bamboo pulp fiber, bleached hardwood pulp fiber, and bleached coniferous pulp fiber respectively, mixing and refining the raw materials to obtain fiber pulp; S200, sending the fiber slurry into a slurry preparation tank, adding lignin sulfonate, wet strength agent, glass powder, and aluminum sulfate to obtain a mixed slurry; S300, the mixed slurry is subjected to screen papermaking, pressing and dehydrating, drying, calendering, and sizing to obtain the coated paper cup base paper; Wherein, the glass powder is subjected to silanization modification treatment.
2. The production process according to claim 1, It is characterized in that S100 specifically includes: S110, weighing 5 to 10 parts by mass of bamboo pulp fiber, 15 to 20 parts by mass of bleached hardwood pulp fiber, and 100 parts by mass of bleached coniferous wood pulp fiber; S120, beating the bamboo pulp fibers to a temperature of 30°SR to 35°SR to obtain bamboo pulp; S130, beating the bleached hardwood pulp fibers and the bleached softwood pulp fibers to 28°SR to 32°SR, respectively, to obtain hardwood pulp and softwood pulp; S140, mixing the bamboo pulp, the hardwood pulp and the softwood pulp, and refining the pulp to 38°SR to 42°SR to obtain the fiber pulp.
3. The production process according to claim 1, It is characterized in that S200 specifically includes: S210, weighing 2 to 4 parts by mass of lignin sulfonate, 2 to 4 parts by mass of wet strength agent, and 5 to 10 parts by mass of glass powder; S220, sending the fiber slurry into a slurry mixing tank, first adding the lignin sulfonate and the wet strength agent and mixing them evenly, then adding the glass powder, and finally gradually adding the aluminum sulfate until the pH value is adjusted to 7.5 to 8.5 to obtain the mixed slurry.
4. The production process according to any one of claims 1 to 3, It is characterized in that The glass powder is fluorophosphate glass powder.
5. The production process according to any one of claims 1 to 3, It is characterized in that The glass powder is prepared by the following steps: S410, weighing materials according to the molar percentage of sodium fluoride: magnesium fluoride: calcium fluoride: aluminum oxide: phosphorus pentoxide = (12-14): (6-10): (8-12): (15-20): (45-55), grinding and mixing them evenly to obtain a glass matrix; S420, heating and melting the glass matrix to obtain glass liquid; S430, casting the glass liquid into a shape, and annealing it to obtain a glass body; S440, crushing and grinding the glass body to obtain the glass powder.
6. The production process according to claim 5, It is characterized in that The temperature condition of the heating and melting is 1280° C. to 1350° C., and the time of the heating and melting is 1 h to 1.5 h.
7. The production process according to claim 5, It is characterized in that The annealing temperature condition is 500° C. to 550° C., and the annealing time is 2 h to 3 h.
8. The production process according to any one of claims 1 to 3, It is characterized in that The silanization modification treatment is carried out by the following steps: S510, mixing and stirring the acetic acid, the water, and the 3-aminopropyltriethoxysilane in a mass ratio of acetic acid: water: 3-aminopropyltriethoxysilane = (10-20): (40-60): 100 to obtain a silane hydrolyzate; S520, adding the glass powder to the silane hydrolyzate according to a mass ratio of glass powder: silane hydrolyzate = (20-25): 100 to obtain a suspension; S530, adding the N,N-dimethyl oxalic acid and the dimethyl sulfate to the suspension in a mass ratio of N,N-dimethyl oxalic acid: dimethyl sulfate: glass powder = (4-6): (4-6): (20-25) to react and obtain the glass powder that has undergone the silanization modification treatment.
9. The production process according to claim 8, It is characterized in that S530 specifically includes: S531, sending the suspension into a reaction kettle, heating it to 40°C to 45°C, and stirring the reaction for 3h to 4h; S532, adding the N,N-dimethyl oxalic acid and toluene having a mass of 4 to 5 times that of the N,N-dimethyl oxalic acid into the reactor, stirring the reaction at a temperature of 100° C. to 120° C. for 3 to 4 hours, and removing the toluene by distillation under reduced pressure; S533, adding the dimethyl sulfate and acetone in an amount 4 to 5 times the amount of the dimethyl sulfate into the reactor, stirring the reaction at a temperature of 80° C. to 100° C. for 0.5 h to 1 h, and removing the acetone under reduced pressure to obtain the glass powder that has undergone the silanization modification treatment.
10. A coated paper cup base paper, It is characterized in that The coated paper cup base paper is obtained by the production process according to any one of claims 1 to 9.
